Barriers and Facilitators to Substance Use Disorder Treatment in Low-and Middle-Income Countries: A Qualitative Review Synthesis. (7th June 2021) - Sarkar, Siddharth; Tom, Ashlyn; Mandal, Piyali
Abstract: Background and aims: One of the ways to address the treatment gap for substance use disorders is to understand the barriers and facilitators to treatment. This study aimed to synthesize the literature on barriers and facilitators of treatment in Low- and Middle-Income Countries (LMICs). Methods: We search Medline electronic database to identify English language peer reviewed empirical studies, both qualitative and quantitative which reported barriers and/or facilitators of treatment of substance use disorders. Results: Of 1389 titles, we selected 28 studies (14 were qualitative and 14 quantitative studies). The sample sizes of the qualitative studies ranged from 11 to 235. The majority of studies were from community or clinic settings. A wide range of barriers and facilitators were identified from the qualitative studies and were synthesized according to perceived susceptibility/seriousness, self-efficacy, perceived costs, perceived benefits, and cues to action. Most of the quantitative studies were community-based cross sectional-observational by design. Commonly identified barriers in these quantitative studies were perceived lack of problem or lack of need for treatment and low motivation whereas factors such as good family support and availability of effective treatment was found to facilitate substance use disorder treatment. Conclusion: There are a wide range of barriers that hinder the substance use disorder treatment as well as certain factors that facilitate the treatment. Addressing them can help to minimize the treatment gap, which in turn can help in reducing the familial and social burden due to substance use disorders.